PENGARUH PAJAK DAERAH DAN DANA ALOKASI UMUM TERHADAP PENDAPATAN ASLI DAERAH DENGAN BELANJA MODAL SEBAGAI VARIABEL INTERVANING (Studi Pada Pemerintah Kabupaten/Kota Jawa Tengah Pada Tahun 2010-2013) - Wahyuning Retno Pawitrasari, 11.05.52.0040; Jaeni, Jaeni (Students Journal of Accounting and Banking, 2015)
This research was conducted to analyze the influence of local tax and Revenue allocation of Public Funds against the Original Area with the capital expenditures as the variable internaving. The object of this research is the whole district/town in Central Java province consists of 35 Kabupaten/Kota. This study uses secondary data from local government BUDGETS and analyzed with path analysis. The results showed (1) there is a positive influence and significant tax areas towards capital expenditure, (2) there is a significant and positive influence of the General Allocation of funds towards capital expenditure, (3) there is a significant and positive influence of local tax Revenue Expenditure against Original Area, (4) there is a significant and positive influence of the General Allocation Funds against the original Revenue areas, (5) there is a positive and significant influence of capital expenditures against Revenue Against the original Area (6) the variable capital expenditures are not proven to mediate the influence of Regional Taxes and funds Allocation against the original Revenue areas.Keywords: Regional Tax (P_Daerah), General Allocation Funds (DAU), Capital Expenditures (BM), and The Original Area Revenue (PAD)